Peran Bukti Tertulis dan Saksi dalam Membuktikan Hak Atas Harta Bersama: Studi Kasus Putusan Pengadilan Agama Salatiga Nomor 70/Pdt.G/2024/Pa.Sal - Ziadaturrahmah; Itsna Hapsari (Jurnal Hukum Respublica, 2024)
The process of dividing joint assets after a divorce often leads to disputes, especially when it comes to proving ownership rights over those assets. This research analyzes the role of written evidence and witness testimony in the case of the Salatiga Religious Court Decision Number 70/Pdt.G/2024/PA.Sal. Written evidence, such as land certificates and agreement documents, serves as the basis for the panel of judges in assessing claims to joint assets, as it provides objective information. However, witness testimony is also crucial in strengthening or weakening claims, providing a more personal perspective. The panel of judges assesses the credibility of witness testimony by considering consistency, relevance, and logic, making both written evidence and witness testimony crucial in determining ownership rights over joint assets. keywords: Shared Assets, Written Evidence, Witness.